The Lived Experience of Nursing Students from Student Work in Clinical Environments: A Hermeneutic Phenomenological Study - Hamidreza Haririan; Hadi Hassankhani; Joanne E Porter (Journal of Caring Sciences)
Introduction: Undergraduate nursing students often work part-time or even full-time while studying at university completing their bachelor’s degrees. The aim of this study is to explain the meaning of the lived experiences of nursing students working as students in clinical field. Methods: A phenomenological study was conducted at the nursing and midwifery school of Tabriz, Iran. Purposefully, 20 baccalaureate nursing students with experience working as student worker nurses were recruited. The sample size was determined according to data saturation. Semi-structured, face-to-face interviews were held with the participants over 3 months (April 2020 to June 2020), and Van Manen’s hermeneutic phenomenological approach was used to analyze the data. Results: Five main themes extracted from the data analysis, including "students’ clinical competency", "nurse-student relationships", "shift work", "mislearning", and "chaotic wards". A further 12 sub-themes extracted under the five main themes. Conclusion: The work of nursing students in clinical environments as student worker nurses is a two-dimensional phenomenon with advantages and disadvantages. The benefits are improving the nursing students’ clinical and communication skills, increasing their self-confidence, learning and practicing discipline and nursing responsibilities, and the disadvantages are facing reality shock stress, and mislearning.